AN EFFICIENT AUTOMATIC ENERGY METER SYSTEM WITH POWER THEFT DETECTOR USING WIRELESS TECHNOLOGY - raja R, Pradeep; S M, Ramesh (IJRDO - Journal of Electrical And Electronics Engineering, 2015)
Within the resent technology development everything became machine-driven .automatic energy meter (aem) is one in every of them. During this automatic energy meter amount of power consumption is calculated on monthly basis and therefore the calculated knowledge (amount of power consumption) is send to the electricity board for asking and eb once more remit the bill quantity to the each user. This energy meter conjointly alert the eb just in case of any detection of power larceny .this system uses atmega microcontroller for assortment and manipulation of knowledge and therefore the technology used here for communication is gsm technology.